The Effects of Teaching Media and Retelling Story Towards Students’ Speaking Ability At Private Madrasah Aliyah In Bandar Lampung - D, Darwissyah Irwan (Universitas Islam Negeri Raden Intan Lampung, 2016)
This research is conducted in private Madrasah Aliyah in Bandar Lampung and aimed to find the effect of using teaching media upon students’ speaking ability. And to find out the effect of retelling story upon students’ speaking ability, Furthermore to find out the interaction effects of using teaching media and retelling story upon students’ skill in speaking ability. The research methodology used experiment. The sample is 56 students who are chosen randomly from private Madrasah Aliyah in Bandar Lampung, then divide the sample into two classes. The first class contain 28 students as experiment class, and the second class contain 28 students as class control. Data collection by teaching them about retelling story using audio visual media and then test their speaking ability. Data analysis is using descriptive statistics, normality test, homogeneity test, and two-way ANNOVA to test the hypothesis by using SPPS 20. Research result : 1) There is no significant effect of teaching media towards students’ speaking ability. This is proved by the result of Fo= 0.001 with sig. 0.987 > 0.05, then the hypothesis (H1) is rejected 2) There is significant effect of retelling story towards students’ speaking ability. This is proved by the result of Fo= 6.52 with sig. 0.000<0.05 3) There are no significant interaction effects of teaching media and retellinig story towards students’ speaking ability. This is proved by the result of Fo =0.704 with sig. 0.648 > 0.05.